Efektivitas Model Pbl Berbantuan Video Animasi Berbasis Animaker Terhadap Hasil Belajar Bahasa Indonesia Materi Teks Narasi Kelas IV SD - Salsabila Nailul Muna; Sri Utaminingsih; Rani Setiawaty (Journal on Education, 2025)
This study addresses the low writing skills of students in composing written work. It aims to analyze the differences in Pretest and Posttest scores and measure the improvement in learning outcomes after applying the Problem-Based Learning (PBL) model assisted by Animaker-based video animation in fourth-grade narrative text lessons.This pre-experimental quantitative study involved 17 fourth-grade students at SDN Sugiharjo 02. Data collection included tests and non-test methods, analyzed using the normality test, Paired Samples T-test, and N-Gain test with SPSS 21. The Paired Samples T-test showed a significant difference (Sig. 0.000 < 0.05), with Pretest scores averaging 55.29 and Posttest scores 80.82. The N-Gain test indicated a 56% improvement, categorized as medium. In conclusion, applying the PBL model with Animaker-based animation videos significantly improves students' narrative text learning outcomes.